Peningkatan Marketing Online Inovation untuk Meningkatkan Penjualan pada Usaha Mikro Kecil Menengah (UMKM) Amplang Kuku Macan Karya Eka - Ugroseno Damara Prasadhana Handoyo; Yudi Herwanto; Nur Tarbiyah; Musliani Musliani; Amanda Fitriyani (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Small-scale economic activities, such as micro, small, and medium enterprises (MSMEs), play a vital role in a region's economy. MSMEs need to be protected and empowered to prevent unfair competition between businesses, especially those involving large-scale businesses. One example of an MSME with great potential is the amplang (rice crackers) manufacturing business, a typical souvenir from Balikpapan. Amplang has a distinctive taste and is attractive to tourists visiting the city, and has the potential to be further developed in the future. However, during the community service process, several problems were discovered among these MSMEs. One of the main problems is the lack of online product marketing expansion. These MSMEs still rely on traditional marketing methods, which are limited to direct sales or through local markets. However, with technological developments and high internet usage, the use of social media for product promotion can have a significant impact on increasing sales and market reach. To address this issue, market share expansion was carried out by utilizing social media, which has not previously been used by these MSMEs. Social media platforms like Instagram, Facebook, and WhatsApp can be highly effective platforms for introducing amplang products to a wider market, both locally, regionally, and nationally. Furthermore, this community service program also provides business development assistance by providing training to MSMEs in social media management, engaging content creation, and appropriate digital marketing strategies. With this introduction to online marketing and mentoring, it is hoped that amplang MSMEs in Balikpapan can better develop their businesses, expand their market reach, and increase their competitiveness in an increasingly competitive market.